The Effect of Leadership Style and Work Climate on Employee Performance In The Population and Family Planning Department of Manado City - Winokan, Jeanny Yola; Bogar, Wilson; Watung, Sjeddie R.; Mandagi, Marthinus (Technium Social Sciences Journal, 2022)
The success of an organization is closely related to employee performance. It can even be said that employee performance is one indicator of its success. Employee performance determines the organization’s success if it can carry out its duties and functions appropriately and adequately in realizing the set organizational goals. The purpose of this article is to measure Performance which is influenced by leadership style and work climate in Manado city. Researchers use this type of research with a quantitative approach. Researchers used a cross-sectional design to obtain information from respondents through a researched sample. The method of this study requires the variables to be measured by surveying the selected model. This quantitative approach is used to measure the level of success in the influence of leadership style and work climate on employee performance at the Manado City Population Control and Family Planning Office. The technique of collecting data and information in this quantitative approach is a questionnaire. The data method analysis in this study uses statistics, namely inferential statistics. Inferential statistics used in this study are parametric. The statistic is helpful for testing population parameters through sample data. This test population parameter is called a statistical hypothesis test.Parametric statistics requires the fulfillment of many assumptions. The results showed that leadership style significantly affected the employees’ Performance at the Office of Population Control and Family Planning in Manado City with a contribution of 3.059 or 0.031%. So it can be concluded that the better the Leadership Style, the higher the performance of employees at the Office of Population and Family Control. Manado City Planning. Work climate does not significantly affect employee performance at the Manado City Population Control and Family Planning Office because it does not contribute to the dependent variable. The influence of leadership style and work climate together on the Performance of employees in the Department of Population Control and Family Planning Manado City is 11.3%.